Mirror energy differences as a probe into neutron skin evolution. (December 2020) - Boso, A.; Lenzi, S. M.; Recchia, F.; Bonnard, J.; Zuker, A. P.
Abstract: Experimental information on charge nuclear radii is limited to ground or isomeric states in stable nuclei; the measurement of neutron radii is even more challenging. In this contribution we present an innovative approach which gives direct insight into the nuclear radii of excited states from the study of Mirror energy differences (MED). MED are a direct consequence of isospin symmetry breaking and their study has proved to give precious information on different nuclear structure features. We report the results of an experiment performed in GANIL to study the MED in rotational bands in mirror nuclei 23 Mg– 23 Na. State-of-the-art shell model calculations have been performed to interpret the data. This allowed to extract information on the evolution of the nuclear skin along excited states and its correlation with the difference between neutron and proton occupation numbers of the s1/2 orbital.